A study of internal fire whirl in a vertical shaft model with partially open roof. (July 2018) - Su, ChungHwei; Bai, JiaHong; Hung, H.Y.; Chow, W.K.; Chow, C.L.
Highlights: Internal fire whirl (IFW) can be created in vertical space in high-rise buildings. IFW can be generated even when the ceiling is partly open for smoke extraction. Two scenarios studied: with front-half covered roof and rear-half covered roof. Compared to closed-roof case, IFW was created earlier in partly opened roof cases. Smoke layer thickness and temperature were reduced with a half-closed roof model. Abstract: An internal fire whirl (IFW) can be generated readily in a tall vertical shaft model under appropriate ventilation provisions. IFW inside a shaft model with corner gap ventilation and closed roof has been reported earlier. It is demonstrated in this paper by scale modeling experiment that an IFW can also be generated even when the ceiling is partly open for smoke extraction. A shaft model of width 34 cm, length 35 cm and height 145 cm, with a 3.6-cm corner gap to provide ventilation on the side. A 7-cm diameter fuel tray of n-propanol was used. Fire in the shaft model was studied under two scenarios, with front-half covered roof and rear-half covered roof (relative to the position of the gap). Background-oriented Schlieren (BOS) technique was applied to measure the neutral plane height across the corner gap. Thermocouples were used to measure smoke temperature and to counter-check results from the BOS technique. Compared with the closed-roof model, IFW was generated at an earlier time, and fuel burning rate was higher in the partly opened roof scenarios. In addition, the smoke layer was kept at a higher level and had a lower temperature.